Analysis of the elastic-plastic behavior of silicon anodes for solid-state batteries based on a coupled thermal-mechanical-electrochemical model - Liu, Zhihao; Liu, Jiatang; Yan, Jiang; Zhou, Jianqiu (Journal of energy storage, 2025)
All-solid-state batteries (ASSBs) are currently the most desirable power source. However, during operation, all-solid-state batteries are limited by problems at the electrode/solid electrolyte interface. Among other things, the batteries are subject to elastic and inelastic deformations due to periodic expansion and contraction, which in turn induce irreversible plastic deformation. In this study, a complete coupled thermal-force-chemical model of ASSB is constructed. The effects of concentration-related material properties on electrode strain accumulation and the elastic-plastic behavior exhibited by the Si negative electrode during charging and discharging are investigated in depth. The results show that mechanical degradation in the form of ratchet deformation occurs at different locations of the electrode during cyclic charging and discharging of the ASSB. The selection of appropriate constraints can provide space for the silicon electrode to expand, which may reduce the ratchet deformation, while appropriate external pressures mitigate the accumulated plastic strain of the electrode, and excessive external loads are detrimental. The developed model may help in the design of silicon negative electrode ASSBs and provides a theoretical approach to extend the cycle life of the battery. •Multi-physics field model of solid-state battery constructed considering plastic deformation of silicon•Discuss the evolution of plastic strain during charging and discharging process•Consideration of lithium-ion induced material softening•Appropriate external pressure can mitigate the plastic accumulation of silicon•Fixation mode will affect the lifetime of silicon-based solid-state batteries.